Challenges and aspirations of neurosurgery residents in Germany : Insights from a questionnaire-based survey - Omer, Mazin; Machetanz, Kathrin; Lawson McLean, Anna C.; Ahmed, Mamoun; Fadlalla, Mohamed; Farzullayev, Jeyhun; Maurer, Stefanie; Alhamdan, Akram A.; Nguyen, Thuy Linh; Beck, Jürgen; Posti, Jussi P. (Elsevier, 2025)
Objective: Neurosurgery residents in Germany face numerous challenges including receiving comprehensive surgical training with adequate learning opportunities, achieving balanced work life equilibrium, maintaining a positive work environment and navigating career prospects. The objectives of this study are to assess overall satisfaction with the training program, identify factors contributing to dissatisfaction, explore various dimensions of the training program, evaluate the psychological well-being of residents, and ascertain their preferences for future subspecialties.
Methods: A questionnaire-based survey was conducted anonymously among neurosurgery residents from various training hospitals, nationwide. The survey utilized a quantitative questionnaire as data collection tool. The data collection took place from June 2021 to January 2023.
Results: The survey encompassed 120 neurosurgery residents, with a gender distribution of 55 % male and 45 % female. The respondents were primarily from university hospitals (53 %), followed by community hospitals (38 %) and private hospitals (9 %). In terms of training program satisfaction, 37 % reported moderate satisfaction, 39 % indicated below-moderate satisfaction, and 28 % experienced above-moderate satisfaction. The predominant causes of dissatisfaction identified were insufficient surgical exposure (reported by 39 % of respondents), suboptimal educational content (38 %), and inadequate research opportunities (32 %). Additionally, 24 % of respondents highlighted psychological stress, and 36 % reported frequent experiences of burnout. A majority (63 %) indicated a workload of 60-80 h weekly. About half of the residents indicated a future specialization interest in neurosurgical oncology.
Conclusion: The results of the survey findings provide valuable insights into the challenges and aspirations of neurosurgery trainees in Germany. These results serve as a basis for improving the training system, enhancing the working environment, and guiding future planning in this field. To optimize the training of residents, it is important to address issues such as limited surgical and research opportunities and psychological well-being. The expressed interest in subspecializing offers guidance for shaping the training program's future direction.